Four novel genes associated with longevity found in Cane corso purebred dogs - Korec, Evžen; Ungrová, Lenka; Hejnar, Jiří; Grieblová, Adéla (BMC veterinary research, 2022)
BACKGROUND: Longevity-related genes have been found in several animal species as well as in humans. The goal of this study was to perform genetic analysis of long-lived Cane corso dogs with the aim to find genes that are associated with longevity. RESULTS: SNPs with particular nucleotides were significantly overrepresented in long-lived dogs in four genes, TDRP, MC2R, FBXO25 and FBXL21. In FBXL21, the longevity-associated SNP localises to the exon. In the FBXL21 protein, tryptophan in long-lived dogs replaced arginine present in reference dogs. CONCLUSIONS: Four SNPs associated with longevity in dogs were identified using GWAS and validated by DNA sequencing. We conclude that genes TDRP, MC2R, FBXO25 and FBXL21 are associated with longevity in Cane corso dogs.
Keywords: psi; jednonukleotidový polymorfismus; hole; Canes; Longevity; Polymorphism, Single Nucleotide; GWAS; Longevity-associated genes; Animals; Dogs; Longevity testing; zvířata; Extending lifespan; Cane corso Italiano dog; dlouhověkost